Análisis de la seguridad de datos en la arquitectura de software como servicio (SaaS). - Jaramillo Malla, Esther Elizabeth (2017)
The present work of titration is based on the data security analysis of the SaaS architecture of cloud computing, is done in order that organizations with a basis to perform a prior analysis to the service provider who wish to contract, has been Evidenced the need to have a guide to data security analysis that do not offer this model, since institutions make use of this service strictly by a necessity leaving behind the security issue, it is a highly important factor for any Company as the data is a transcendental asset for the perpetuity and continuity of the functions of an organization. Corporate espionage has become stronger in recent years with the immersion of technology. This problem is exacerbated by the use of cloud services because data travels around the world, ignoring the security policies of the data that The son Applicable in each country thus leaving our data a disposition of the owners of the centers where it is stored, this type of vulnerabilities in the SaaS architecture are exploited by intruders to obtain information that can lead to competition to bankruptcy, as well To the institutions that make use of this model and do not take into account the contracts and the policies that must be delivered by the suppliers to arrive at a consensual agreement with the client; Customers must have information security and that is the most important asset of the whole entity, and is susceptible to theft, loss, modifications, constituting itself as an asset too vulnerable, for that reason The security terms of the data that they offer The provider to be broadcast in the cloud.